Implementasi Pendampingan Pemeriksaan Awal Terhadap Anak yang Berhadapan dengan Hukum oleh Pembimbing Kemasyarakatan pada Balai Pemasyarakatan Kelas I Manado - Pahotan Butarbutar; Devy Sondakh; Caecilia Waha (Departement of Mathematics Education, 2023)
Children, including children who are in conflict with the law, are the future of the nation whose rights must be fulfilled so that they can grow and develop according to their potential. Probation Officer at Correctional Hall have the authority to provide assistance during the initial investigations by the police. This study aims to examine the rules and implementation of assistance for initial examination of children in conflict with the law by Probation Officer at the Class I Manado Correctional Hall. The method used in this research is empirical normative legal research. The results of the study show that Probation Odfficer in implementing initial examination assistance for children in conflict with the law carry out the role of researcher, mediator, and carry out a supervisory role. Probation Officers provide recommendations in the form of social research results (Penelitian Kemasyarakatan/Litmas) which are also a requirement in the process of investigation, prosecution and court hearings. In order for the implementation of assistance to run optimally, the advice that can be given is that it is hoped that there will be better coordination between law enforcers, be it the police, prosecutors, courts, and Correctional Hall, and it is hoped that Probation Officers will develop knowledge in fields other than law, namely science social welfare, psychology, and sociology.